A PPAR‐gamma agonist protects from radiation‐induced intestinal toxicity. Issue 2 (1st March 2017) - Mangoni, Monica; Sottili, Mariangela; Gerini, Chiara; Desideri, Isacco; Bastida, Cinzia; Pallotta, Stefania; Castiglione, Francesca; Bonomo, Pierluigi; Meattini, Icro; Greto, Daniela; Cappelli, Sabrina; Di Brina, Lucia; et al.
Abstract : Objective: Because of its anti‐inflammatory, anti‐fibrotic, anti‐apoptotic and anti‐neoplastic properties, the PPAR‐γ agonist rosiglitazone is an interesting drug for investigating for use in the prevention and treatment of radiation‐induced intestinal damage. We aimed to evaluate the radioprotective effect of rosiglitazone in a murine model of acute intestinal damage, assessing whether radioprotection is selective for normal tissues or also occurs in tumour cells. Methods: Mice were total‐body irradiated (12 Gy), with or without rosiglitazone (5 mg/kg/day). After 24 and 72 hours, mice were sacrificed and the jejunum was collected. HT‐29 human colon cancer cells were irradiated with a single dose of 2 (1000 cells), 4 (1500 cells) or 6 (2000 cells) Gy, with or without adding rosiglitazone (20 µM) 1 hour before irradiation. HT‐29‐xenografted CD1 mice were irradiated (16 Gy) with or without rosiglitazone; tumour volumes were measured for 33 days. Results: Rosiglitazone markedly reduced histological signs of altered bowel structures, that is, villi shortening, submucosal thickening, necrotic changes in crypts, oedema, apoptosis, and inflammatory infiltrate induced by irradiation. Rosiglitazone significantly decreased p‐NF‐kB p65 phosphorylation and TGFβ protein expression at 24 and 72 hours post‐irradiation and significantly decreased gene expression of Collagen1, Mmp13, Tnfα and Bax at 24 hours and p53 at 72 hours post‐irradiation. Rosiglitazone reduced HT‐29 clonogenic survival, but only produced a slight reduction of xenograft tumour growth. Conclusion: Rosiglitazone exerts a protective effect on normal tissues and reduces alterations in bowel structures and inflammation in a radiation‐induced bowel toxicity model, without interfering with the radiation effect on HT‐29 cancer cells. PPAR‐γ agonists should be further investigated for their application in abdominal and pelvic irradiation.